2009
DOI: 10.1111/j.1365-2567.2009.03109.x
|View full text |Cite
|
Sign up to set email alerts
|

A tolerogenic peptide down‐regulates mature B cells in bone marrow of lupus‐afflicted mice by inhibition of interleukin‐7, leading to apoptosis

Abstract: Summary Systemic lupus erythematosus (SLE) is an autoimmune disease mediated by T and B cells. It is characterized by a variety of autoantibodies and systemic clinical manifestations. A tolerogenic peptide, designated hCDR1, ameliorated the serological and clinical manifestations of SLE in both spontaneous and induced models of lupus. In the present study, we evaluated the status of mature B cells in the bone marrow (BM) of SLE‐afflicted mice, and determined the effect of treatment with the tolerogenic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Those beneficial effects resulted from the effects of hCDR1 on different immune cell types (including dendritic [22], T [9], [17], [34] and B cells [20], [21], [35]) and on cytokines [9], [11]. Thus, hCDR1 down regulated (in vivo and in vitro, in murine SLE models and in human lupus) pro-inflammatory cytokines [11], [23], [24], apoptotic factors [18], [19], [23], [24], [36], B-cell stimulatory factors (BAFF/BLyS) [20], [24] and up regulated immunosuppressive cytokines [9], [11], [23], [24], [37] with the induction of CD4+CD25+FoxP3+regulatory T-cells [15], [23].…”
Section: Discussionmentioning
confidence: 99%
“…Those beneficial effects resulted from the effects of hCDR1 on different immune cell types (including dendritic [22], T [9], [17], [34] and B cells [20], [21], [35]) and on cytokines [9], [11]. Thus, hCDR1 down regulated (in vivo and in vitro, in murine SLE models and in human lupus) pro-inflammatory cytokines [11], [23], [24], apoptotic factors [18], [19], [23], [24], [36], B-cell stimulatory factors (BAFF/BLyS) [20], [24] and up regulated immunosuppressive cytokines [9], [11], [23], [24], [37] with the induction of CD4+CD25+FoxP3+regulatory T-cells [15], [23].…”
Section: Discussionmentioning
confidence: 99%
“…The reduced levels of BAFF correlated with reduced rate of maturation and differentiation of B cells and decrease in integrin expression. Recent studies provided further evidence of targeting of BAFF/BLys and APRIL in the management of lupus ( 86 88 ); and another study reported the effect of hCDR1 on IL-7 and apoptosis ( 89 ) and showed the rate of apoptosis is reduced with hCDR1 treatment in lupus mice. Bcl2 and Bcl- XL levels were further reduced, and this was associated with reduced activation of T and B cells ( 90 ).…”
Section: Discussionmentioning
confidence: 99%